Translating “Under the Sign of Invention”: Gilberto Gil’s Song Lyric Translation - Cintrão, Heloísa (Meta, 2009)
AbstractThe translation of song lyrics shares in the difficulties of constrained translation, as well as in the impossibilities of poetic translation. In Gilberto Gil’s adaptation of the song “I just called to say I love you” by Stevie Wonder, two translation procedures stand out: (1) to take broad semantic fields as translation units, and (2) to opt for cultural adaptation in terms of the translation’s poles of domesticating/foreignizing. The way Gil faces up to the challenges of the translation of the song is consistent with Haroldo de Campos ideas on transcreation.